DESENVOLVIMENTO DE PODISUS NIGRISPINUS (DALLAS, 1851) (HEMIPTERA: PENTATOMIDAE) ALIMENTADO COM LAGARTAS DE DIATRAEA SACCHARALIS (FABRICIUS, 1794) (LEPIDOPTERA: CRAMBIDAE) - Vacari, A.m. [UNESP]; Otuka, A.k. [UNESP]; De Bortoli, S.a. [UNESP] (Instituto Biológico, 2022)
The aim of this study was to evaluate the biological aspects of Podisus nigrispinus (Dallas) fed on Diatraea saccharalis (Fabricius) caterpillars. The eggs (200) used for the trial were obtained from the mass rearing of the Laboratory of Biology and Insect Rearing of the Department of Plant Health, at FCAV/UNESP. The eggs were maintained in an acclimatized room (T = 25 ± 1° C, photophase = 12h and RH = 70 ± 10%), where the following parameters were evaluated: embrionary period and egg viability. When the nymphs reached the 2nd instar, the insects were individualized in Petri dishes, where the following parameters were evaluated: nymph viability, duration of the nymph period and weight of 5th instar nymph. In the adult stage, the insects were coupled in Petri dishes, where the following parameters were evaluated: preoviposition, oviposition and post oviposition periods; adult longevity; adult weight after emergence and at 20 days old; fecundity; number of egg masses per female; number of eggs per egg mass; egg viability and embrionary period. The parameters of the fertility life table were also evaluated. By the results it was possible to conclude that: caterpillars of D. saccharalis were appropriate for P. nigrispinus development, suggesting the possibility of using these prey in mass rearing of this insect.

O objetivo desse trabalho foi avaliar aspectos biológicos de Podisus nigrispinus (Dallas) alimentado com lagartas de Diatraea saccharali(Fabricius). Os ovos (200) utilizados para o experimento foram provenientes da criação massal do Laboratório de Biologia e Criação de Insetos do Departamento de Fitossanidade da FCAV/UNESP. Esses ovos foram mantidos em sala climatizada a 25 ± 1° C, fotofase de 12h e UR de 70 ± 10%, sendo avaliados os parâmetros: período de incubação e viabilidade dos ovos. Ao atingirem o 2o estádio ninfal, os insetos foram individualizados em placas de Petri, onde foram avaliados os parâmetros: viabilidade ninfal, duração do período ninfal e peso das ninfas de 5o estádio. Na fase adulta os insetos foram separados, por casais, em placas de Petri, com os quais foram avaliados os parâmetros: período de préoviposição, oviposição, pós-oviposição, longevidade, peso dos adultos após emergência, peso dos adultos com 20 dias, fecundidade, número de posturas por fêmea, número de ovos por postura, viabilidade dos ovos e período de incubação. Além disso, também foram obtidos os parâmetros da tabela de vida de fertilidade. Pelos resultados verificou-se que lagartas de D. saccharalis foram nutricionalmente adequadas para o desenvolvimento do predador P. nigrispinus, sugerindo a possibilidade de utilização dessa presa em criações massais desse inseto.
DEVELOPMENT OF PODISUS NIGRISPINUS (DALLAS, 1851) (HEMIPTERA: PENTATOMIDAE) FED ON DIATRAEA SACCHARALIS (FABRICIUS, 1794) (LEPIDOPTERA: CRAMBIDAE) CATERPILLARS
Keywords: Asopinae; biology of insects; biological control; predatory stinkbug; Asopinae; biologia de insetos; controle biológico; percevejo predador